Judging judges - Galligan, D (Foundation for Law, Justice and Society, 2007)
The principle of independence of the judiciary, while fundamental to a society based on the rule of law, is sometimes used to preclude the evaluation of courts. Such an approach is mistaken: judges and courts should be both independent and subject to evaluation. How to evaluate judges and courts raises particular issues, such as how to maintain judicial independence and at the same time develop mechanisms of accountability. Few European countries, old democracies as well as new ones, have yet addressed these issues. Evaluation must take a twofold approach to address the distinct exercises of assessing judges individually and the judicial system as a whole. It is necessary with respect to each to devise separate standards of evaluation against which they can be meaningfully assessed. In evaluating judges individually, three types of standards are relevant: qualifications and training, judicial competence, and good conduct.